‘Triple P’ to Improve English Speaking Ability of Students in English Language and Literature Study Program Sawerigading University - Rezkiawati Nazaruddin; Syamsuddin Syamsuddin (Universitas Sulawesi Barat, 2018)
The purpose of this study is to find out whether the triple P model can Improve the students' speaking skills. This research is a Classroom Action Research which applied to the students of English Language and Literature Study Program of Sawerigading University the academic year of 2016/2017. During the learning process, students are taught using ‘Triple P’ model. This model includes three activities; presentation, practice and production. In general it can be concluded that this model could motivate the students to speak confidently in the classroom and showed the improvement of students’ creativity on teaching learning process, their ability to express their own ideas, and their ability to interact or communicate with their friends.